Pregnancy favors the expansion of circulating functional follicular helper T Cells. (June 2017) - Monteiro, Clarice; Kasahara, Taissa M.; Castro, José Roberto; Sacramento, Priscila M.; Hygino, Joana; Centurião, Newton; Cassano, Tatiane; Lopes, Lana M. Ferreira; Leite, Simone; Silva, Vander Guimarães; Gupta, Sudhir; Bento, Cleonice A.M.
Highlights: The pregnancy favors the expansion of CXCR3 + PD-1 + ICOS + TFH cells. The proportion of IL-21 + TFH cells was higher in pregnant women. Serum levels of IgG anti-HBsAg was directly associated with IL-21 + TFH cells. In vivo estrogen levels were correlated with the percentage of IL-21 + TFH cells. Abstract: Pregnancy favors antibody production, and some evidence has suggested a direct effect of estrogen on B cells. The impact of pregnancy on circulating follicular helper T (TFH ) cells, typically identified by the expression of CD45RO and CXCR5, has not been previously investigated. Here, the percentage of TFH cells, co-expressing or not PD-1, ICOS, or CXCR3 markers was significantly higher in pregnant women (PW) as compared with non-pregnant ones (nPW). Furthermore, the percentage of CXCR3 + TFH cells able to produce IL-6, IL-21, and IL-10 was significantly higher in PW than nPW. Interestingly, anti-CMV and anti-HBs antibody titers were significantly higher in the plasma of PW and were directly correlated with IL-21-producing CXCR3 + TFH cells. Finally, peripheral estrogen levels, but not progesterone, were positively related to either PD-1 + CXCR3 + TFH cells or plasma anti-CMV and anti-HBs IgG antibodies. In summary, our data suggests a positive effect of pregnancy on the proportion of CD4 + T cell subset specialized in helping B cells. This phenomenon, which could be related to the high estrogen levels produced during pregnancy, may help to explain why pregnancy favor humoral immunity.